Note:
Your question is a little unclear. But, from my understanding, I assume you may be asking the evaluation of the expression 36x - y when x = 3 and y = -6.
so I will solve based on my assumption which anyways would clear your concept.
Answer:
The value of 36x - y when x = 3 and y = -6 will be: 114
Explanation:
Given
Assuming the expression
36x - y
To Determine
Evaluate 36x - y when x = 3 and y = -6
Given the expression
![36x - y](https://img.qammunity.org/2022/formulas/mathematics/high-school/zu1ljew0brmtvxw5sv12o8v5psbu8svcvo.png)
substitute x = 3 and y = -6 to evaluate the expression
![36x-y= 36(3) - (-6)](https://img.qammunity.org/2022/formulas/mathematics/high-school/w5n8uiwp98w1hbjojhwq15z4rxke7thjfi.png)
![= 108+6](https://img.qammunity.org/2022/formulas/mathematics/high-school/e626u9pcdf66x3bjq0h0dst9z1p9cqkyua.png)
![= 114](https://img.qammunity.org/2022/formulas/mathematics/high-school/9x8i86e9rvifmd5a5lqvpf4x7vf7cz02ys.png)
Therefore, the value of 36x - y when x = 3 and y = -6 will be: 114